Discovery of Epichloë as novel endophytes of Psathyrostachys lanuginosa in China and their alkaloid profiling - Chen, Taixiang; Wang, Tian; Du, Mingxiang; Malik, Kamran; Li, Chunjie; Bao, Gensheng (Frontiers in Microbiology, 2024)
The Epichloë genus represents a significant group of above-ground endophytes extensively researched for their potential applications in agriculture and ecology. Additionally, Epichloë species synthesize bioactive alkaloids, which generally cause health problems in livestock and have detrimental effects on the performance of insect herbivores. Psathyrostachys lanuginosa serves as a valuable forage grass for livestock owing to its high nutritional value and resilience in adverse environmental conditions. Nevertheless, to date, no reports have documented Epichloë as endophytes of P. lanuginosa. In this study, four strains (PF5, PF9, QG2, and QG4) were isolated and identified through morphological, molecular, and phylogenetic analyses as endophytes of P. lanuginosa. Morphological analysis indicated colony characteristics and conidia features consistent with symbiotic Epichloë, with no significant differences observed in growth rates or conidia dimensions among the four strains. Phylogenetic analysis confirmed all strains as E. bromicola. Additionally, alkaloid biosynthetic genes were detected, revealing differences in the potential synthesis of peramine and indole diterpenoid alkaloids among strains from different geographic origins. However, all four E. bromicola strains exhibited similar potential for synthesizing ergot alkaloids, but not loline alkaloids. Overall, this study identified P. lanuginosa as a novel host for E. bromicola and provided insights into the alkaloid profiles of these strains, laying a solid foundation for the scientific and rational utilization of Epichloë resources.